2004
DOI: 10.1001/archpsyc.61.12.1246
|View full text |Cite
|
Sign up to set email alerts
|

A Family Study of Alcohol Dependence

Abstract: The risk of alcohol dependence in relatives of probands compared with controls is increased about 2-fold. The aggregation of antisocial personality disorder, drug dependence, anxiety disorders, and mood disorders suggests common mechanisms for these disorders and alcohol dependence within some families. These data suggest new phenotypes for molecular genetic studies and alternative strategies for studying the heterogeneity of alcohol dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 227 publications
(67 citation statements)
references
References 61 publications
3
63
1
Order By: Relevance
“…Probands were required to meet criteria for DSM-III-R alcohol dependence (42) and Feighner definite alcoholism (43), and to have at least 2 first-degree relatives available for study in the catchment area; all first-degree relatives were sought for baseline and follow-up interviews 5 years later (19, 44). The COGA protocol was approved by the institutional review board at each research site and all subjects provided written informed consent.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Probands were required to meet criteria for DSM-III-R alcohol dependence (42) and Feighner definite alcoholism (43), and to have at least 2 first-degree relatives available for study in the catchment area; all first-degree relatives were sought for baseline and follow-up interviews 5 years later (19, 44). The COGA protocol was approved by the institutional review board at each research site and all subjects provided written informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…Familial influences accounted for 11% of the variance associated with remission in females (attributable to genetic influences shared with AUD) and 37% in males (attributable to environmental influences shared with the co-twin) which decreased the likelihood of remission (36). In the current study we used data from a high-risk family study, the Collaborative Study on the Genetics of Alcoholism (COGA), which has a high prevalence of lifetime AUD in the relatives of probands (19) and thus provides enough AUD-affected, and thus potentially remitted, proband-relative pairs to model persistent AUD, non-abstinent remission, and abstinent remission in both subjects. Greater AUD severity was associated with decreased likelihood of non-abstinent remission and increased likelihood of abstinent remission in population-based data and in previous work in COGA (10, 30, 37), consistent with other studies that found abstinent individuals had more severe AUD histories than non-abstinent individuals (27, 38, 39).…”
Section: Introductionmentioning
confidence: 99%
“…So far, a family history positive for alcohol abuse seems to be the best predictor of one's risk to develop an alcohol addiction [17]. Relatives of alcohol-addicted patients, for example, prefer higher levels of brain alcohol exposure [18] and are at a greater risk to develop an alcohol addiction [19]. …”
Section: Alcohol (Ab)use On the Threshold Of Adulthoodmentioning
confidence: 99%
“…Relatives of alcohol-dependent probands showed significant familial aggregation of ASPD in the Collaborative Study on the Genetics of Alcoholism (COGA) [Nurnberger et al, 2004]. A positive family history of alcoholism is associated with symptoms of ASPD [Grande et al, 1984; Alterman and Cacciola, 1998; Slutske et al, 1998; Jang et al, 2001] and evidence from family and twin studies supports a genetic contribution to the overlap in substance abuse and dependence, conduct disorder (CD), and ASPD [Stallings et al, 1997; Blonigen et al, 2005].…”
Section: Introductionmentioning
confidence: 99%